ASSESSMENT OF METASTATIC BRAIN TUMORS RESPONSE TO STEREOTACTIC RADIOSURGERY WITH DIFFUSION TENSOR IMAGING - A. S. Tokarev; V. N. Stepanov; V. A. Rak (Вестник рентгенологии и радиологии)
Metastatic brain tumors – one of the most actual problems of neurooncology. Currently, whole brain radiotherapy and stereotactic radiosurgery are the main treatment methods of this pathology. The assessment of tumor’s response to irradiation is very important issue in postoperative period. We attempted solve it by using diffusion tensor imaging.